COMPARISON OF CASING MATERIAL SELECTION IN GAS DEEPWATER WELL, CARBON CAPTURE STORAGE WELL, AND GEOTHERMAL WELL - Triveda Fajri, Nugroho
Currently, deepwater resource has been explored since the increasing fossil energy necessity. On the other hand, carbon capture storage (CCS) has been developed in recent years in order to combat global warming effect, whereas geothermal development projects are growing rapidly also as green energy necessity. Although CCS and geothermal drilling are similar to oil and gas drilling, the facts show that there are distinctions that cannot be marginalized in CCS and geothermal well design. Most of CCS and geothermal casing design is adopted from oil and gas design, therefore casing failure is often found when there are no modification made. The casing failure may be caused by failure in design or operation of running in the casing into the hole, or by another factors related to geologic condition of reservoir (i.e. extreme temperature and sour environment of reservoir, etc.)11. In gas deepwater wells, casing failure not only occurred due to high pressure and high temperature but also corrosion problems like in conventional oil and gas well. The main challenges associated with drilling geothermal wells are related mostly to hardness of igneous and metamorphic rocks, which are not commonly found in oil/gas reservoir, high temperature of the formation (average temperature gradient for oil/gas is 50F/100 ft and 12-130F/100 ft or could be more for geothermal formation) and typically under-pressured strata reservoir11, while one of the important wellbore integrity issues in CCS wells is casing failure due to erosion and corrosion by high pressured production fluids10. In casing design, casing material must be selected properly in order to mitigate corrosion as long as project development time. This paper presents comparison of casing material selection in gas deepwater, carbon capture storage, and geothermal well coupled to the case study based on corrosion rate prediction based on wellbore condition (i.e. pressure, temperature, etc.), fluid properties, and geologic environment. Reservoir fluid analysis and production performance analysis also considered in predicting corrosion rate. This study proved that few variables such as CO2, H2S, bicarbonate and chromium content, inclination, temperature, pressure, and pH are key parameters in determining corrosion rate. Temperature and pH significantly affect the corrosion rate in gas deepwater well N, carbon capture storage well F, and geothermal well T beside the composition of CO2 and H2S. Consideration must be made in selecting material for due to high content of CO2 and H2S, especially for CCS well.